Global and Detailed Local Fatigue Assessment of a Container Vessel - A comparison between linear and nonlinear FE-analyses - Tesanovic, Andrea; Knifsund, Camilla (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2012)
Container ships operating in the North Atlantic have a challenging structural design with respect to fatigue. The container vessels are long and slender and they have large openings in the deck. The structural design, in a combination of high wave loads, makes the ship sensitive to fatigue cracks. The estimated fatigue life according to class rule procedures is too short to be realistic in several fatigue-critical locations of container vessels. The class rules mainly base their assumptions on stress-based approach, where high stress-concentration factors are commonly accepted. This could be one of the reasons why plastic deformation occurs locally in ship structures and fatigue cracks appear at an early stage. The objective with this study is to simulate numerically and assess the structural response of a container ship by assuming either linear material, or nonlinear, material response. In order to enable such a study, a hydrodynamic analysis is adopted to simulate the wave-induced structural loads, followed by a linear and nonlinear FE-analysis in order to obtain the structural strength. A long-term fatigue analysis is performed to obtain the critical locations in the ship. A script is created that makes it possible to change between a linear and nonlinear FE-solver. The results from the long-term fatigue analysis indicate that the critical locations exist in the hatch corners, forward engine room bulkhead and in the bilge region. However, the side shell on the port side was chosen for further study. The results from the nonlinear structural FEanalysis indicate that almost no plastic deformation will occur in the critical region of the side shell. Hence, the conclusion was made that a strain-based approach to fatigue is not necessary for this location. A linear structural FE-analysis with the effect from internal ballast water was studied. The results from the linear structural FE-analysis with the effect from internal ballast pressure showed only a small impact on the stress-levels. For future work it is ...